Bulk Viscous String Cosmological Model With Power Law Volumetric Expansion In Teleparallel Gravity - Kalpana Pawar; Dabre, A. K. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
In this paper, we have investigated the Bianchi-type V cosmological model which is spatially homogeneous and anisotropic in presence of bulk viscous fluid containing one-dimensional cosmic string. We have obtained the exact solutions of highly non-linear differential field equations considering the power-law volumetric expansion of the universe and f (T ) = T formalism. Some physical and kinematical properties of the constructed model have been discussed and presented graphically and it is interesting to note that the resultant model resembles the recent observational data. В этой статье исследована космологическая модель типа V Бианки, которая является пространственно однородной и анизотропной в присутствии объемной вязкой жидкости, содержащей одномерную космическую струну. Получены точные решения сильно нелинейных дифференциальных уравнений поля с учетом степенного закона объемного расширения Вселенной f (T ) = T формализма. Некоторые физические и кинематические свойства построенной модели были обсуждены и представлены графически, и интересно отметить, что полученная модель соответствует последним данным наблюдений.
Keywords: Astrophysics